The effect of personality on job performance among salesperson - Nor Farhana, Yusoff (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study aims to identify the effect of Big Five Personality (Openness to Experience, Conscientiousness, Extroversion, Agreeableness, Neuroticism) on job performance among salespersons. Quantitative research methodology is used in this research and data were collected using questionnaires as the instrument. Actual data were collected from 59 salespersons in telco store Perak. The data were analysed using descriptive and inferential studies. Spearman's rho correlation is used to measure the relationship between Big Five personality and job performance. The finding has shown that there are significant relationship between Openness to Experience, Conscientiousness, Extroversion, Agreeableness, Neuroticism and job performance. It showed that agreeableness has the most dominant factor that contribute to the Big Five Personality on job performance. As such researcher recommend including of more types of locations to reduce the biasness of the results and also increase the reliability and accuracy of the data.